2021
DOI: 10.1038/s41535-021-00327-4
|View full text |Cite
|
Sign up to set email alerts
|

Charge density waves in cuprate superconductors beyond the critical doping

Abstract: The unconventional normal-state properties of the cuprates are often discussed in terms of emergent electronic order that onsets below a putative critical doping of xc ≈ 0.19. Charge density wave (CDW) correlations represent one such order; however, experimental evidence for such order generally spans a limited range of doping that falls short of the critical value xc, leading to questions regarding its essential relevance. Here, we use X-ray diffraction to demonstrate that CDW correlations in La2−xSrxCuO4 per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 50 publications
11
47
0
Order By: Relevance
“…The new feature of the experiments is the very broad BP (FWHM~ξ −1~0 .16-0.18 r.l.u. ), by now observed in many other families [55][56][57][58][59][60]. It has many peculiar properties (Figure 11), as follows: (i) it is present up to the highest measured T well above T*(p); (ii) the width (FWHM) and the correlation length are almost constant in T; the corresponding charge fluctuations are then non-critical and do not show any tendency to become critical at any finite T; and (iii) the characteristic energy ω ch has been measured by fitting the dynamical high-resolution spectra on the OP90 (and UD60) samples at T = 90 K, 150 K, 250 K and q = q c .…”
Section: Experimental Observation Of the Scenario Presented Abovementioning
confidence: 79%
“…The new feature of the experiments is the very broad BP (FWHM~ξ −1~0 .16-0.18 r.l.u. ), by now observed in many other families [55][56][57][58][59][60]. It has many peculiar properties (Figure 11), as follows: (i) it is present up to the highest measured T well above T*(p); (ii) the width (FWHM) and the correlation length are almost constant in T; the corresponding charge fluctuations are then non-critical and do not show any tendency to become critical at any finite T; and (iii) the characteristic energy ω ch has been measured by fitting the dynamical high-resolution spectra on the OP90 (and UD60) samples at T = 90 K, 150 K, 250 K and q = q c .…”
Section: Experimental Observation Of the Scenario Presented Abovementioning
confidence: 79%
“…Regarding the parameters of the fluctuations, these were extracted from RXS experiments on a NdBa 2 Cu 3 O 7−y sample, consistently leading to a deviation from linearity below T F L ≈ 100 K in agreement with the resistivity data. Here, we consider the case of Nd-La 2−x Sr x CuO 4 , where resistivity under strong magnetic fields is linear down to T ≈ 5 K. Unfortunately, although RXS experiments recently confirmed also for these cuprates the presence of charge density fluctuations with broad momentum distribution 25 , detailed data are not available to extract their parameters. This is why we assume here that the parameters fitted from RXS data in NdBa 2 Cu 3 O 7−y are still reasonable estimates for Nd-La 2−x Sr x CuO 4 and we therefore use similar values: m = 10 meV,ν = 1.3 eV/(r.l.u.)…”
Section: Resultsmentioning
confidence: 99%
“…Incoherent stripe correlations are also present in the normal state of LSCO [7,8]. Intriguingly, a study of shot noise in tunnel junctions involving LSCO films found evidence for pairs in the the normal state of underdoped samples [82].…”
Section: Pdw Ordermentioning
confidence: 97%
“…Charge order has now been observed in virtually all hole-doped cuprate superconductor families [1][2][3]. In 214 cuprates, such as La 2−x Sr x CuO 4 (LSCO) and La 2−x Ba x CuO 4 (LBCO), the charge-stripe order is generally accompanied by spin-stripe order [4][5][6][7][8], as originally observed in Nd-doped La 2−x Sr x CuO 4 [9,10]; each of these orders breaks the translation symmetry of the square-lattice CuO 2 planes. In a 1996 paper, Kivelson and Emery [11] pointed out the topological character of the combined spin and charge stripe orders.…”
Section: Introductionmentioning
confidence: 99%